Curso técnico médio público em administração: um estudo sobre grades curriculares e formação no período de 1969 a 1982 na cidade de São Paulo - Pequin, Bento Salvio (2015)
The research proposed on this project is to examine the changes in the technical course curriculum administration in the first technical highschool administration of São Paulo created in 1968 and later became the Technical School when it started to integrate the Centro Estadual de Educação Tecnológica Paula Souza CEETEPS. Was guided by questions about what were the technical course curriculum administration of the initial course and what changes have occurred in these Administration Technical Course grids when the Centro Paula Souza started to take responsibility for the schools. This is a research that sought to detect the context in which the course was created to understand it as situated, that is, understanding the relationship between policies action and social and economic characteristics in which this course inception process occurred. For this, we sought to study literature on the decades from 1950 to 1980, information would be extracted from documents the departament of CEETEPS, from the end of the 1960s identifying the decisions that led to the suitability of the technical high school of the state of São Paulo, in facing the legislation. Taken up as a criterion for analysis technical course curriculum administration , the constituent disciplines and course loads of them. In addition, information would be extracted from documents of the Public Archives of the State of São Paulo. Theoretically grounded researched some concepts of Michael W. Apple on curriculum, especially when discussing the concept of hegemony linking culture and economy and the concepts of stability of patterns of change proposed by Ivor Goodson, these standards that exist in reality creating impersonal webs influence. It was possible to verify the persistence of a structure of disciplines that comes from the 1970s, but with evidence of an earlier tradition which come from decades of the early twentieth century. There are variations between hourly loads more than in relation to the disciplines now with a predominance of general training, sometimes with a predominance of specific training